Motor skills and later communication development in early childhood: Results from a population‐based study. (26th March 2020) - Valla, Lisbeth; Slinning, Kari; Kalleson, Runa; Wentzel‐Larsen, Tore; Riiser, Kirsti
Abstract: Background: Motor milestones in infancy are important developmental markers, not only for later motor skills but also for more widespread social, cognitive, and communication development. The aim of the current study was to investigate the relationships between fine and gross motor development in infants at 6 and 12 months of age and communication skills at 24 months of age. Methods: The Ages & Stages Questionnaire (ASQ‐II) was used to measure gross motor, fine motor, and communication skills in a large population‐based sample of 1, 555 infants, recruited from well‐baby clinics in five municipalities in South‐Eastern Norway. Of these, 557 children had valid values of gross and fine motor scores at 6 and 12 months and for communication score at 24 months. The relationships between motor skills at 6 and 12 months and communication skills at 24 months were analysed using a linear regression analysis. Results: Gross motor skills at 6 months were positively associated with communication skills at 24 months (coefficients 0.09, p = 0.036) and fine motor skills at 12 months were positively associated with communication skills at 24 months (coefficient 0.23, p < 0.001). We did not find clear evidence for a relationship between gross motor skills at 12 months and communication skills at 24 months (coefficient 0.05, p = 0.126) or between fine motor skills at 6 months and communication skills at 24 months (coefficient 0.08, p = 0.098). Conclusion: The present study supports previous research showing associations between early motor development and later communication development in infancy. Targeted intervention should be considered with at‐risk infants.